2012
DOI: 10.4028/www.scientific.net/kem.510-511.201
|View full text |Cite
|
Sign up to set email alerts
|

Role of Synthesis Parameters on Structural and Electrical Properties of M-Type Hexa-Ferrites

Abstract: Phase purity, particle size and its distribution contributes a lot to the physical properties of M-type hexa-ferrites. These parameters are strongly influenced by the variation in synthesis parameters. In the present work, effect of synthesis parameters such as molar ratio (Fe/Sr) and volume rate of addition of precipitating agent on M-type hexa-ferrite (SrFe12O19) prepared by co-precipitation method have been investigated systematically. The molar ratio (Fe/Sr) in SrFe12O19was varied as 12, 11, 10, 09, and 08… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The study indicated that, as money rises, environmental quality improves at first but ultimately deteriorates. [67] investigate the relationship between carbon dioxide emissions, income, energy use, and foreign trade in Pakistan from 1972 to 2008. Using the Johansen approach, the study revealed a quadratic long-run link between CO 2 emissions and income, confirming the existence of EKC in Pakistan.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…The study indicated that, as money rises, environmental quality improves at first but ultimately deteriorates. [67] investigate the relationship between carbon dioxide emissions, income, energy use, and foreign trade in Pakistan from 1972 to 2008. Using the Johansen approach, the study revealed a quadratic long-run link between CO 2 emissions and income, confirming the existence of EKC in Pakistan.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%